Epitope Structure of the Bordetella pertussis Protein P.69 Pertactin, a Major Vaccine Component and Protective Antigen - Hijnen, Marcel (American Society for Microbiology, 2004)
Bordetella pertussis is reemerging in several countries with a traditionally high vaccine uptake. An analysis of clinical isolates revealed antigenic divergence between vaccine strains and circulating strains with respect to P.69 pertactin. Polymorphisms in P.69 pertactin are mainly limited to regions comprised of amino acid repeats, designated region 1 and region 2. Region 1 flanks the RGD motif, which is involved in adherence. Although antibodies against P.69 pertactin are implicated in protective immunity, little is known about the structure and location of its epitopes. Here we describe the identification by pepscan analysis of the locations of mainly linear epitopes recognized by human sera and mouse monoclonal antibodies (MAbs). A total of 24 epitopes were identified, and of these only 2 were recognized by both MAbs and human antibodies in serum. A number of immunodominant epitopes were identified which were recognized by 78 to 93% of the human sera tested. Blocking experiments indicated the presence of high-avidity human antibodies against conformational epitopes. Human antibodies against linear epitopes had much lower avidities, as they were unable to block MAbs. Pepscan analyses revealed several MAbs which bound to both region 1 and region 2. The two regions are separated by 289 amino acids in the primary structure, and we discuss the possibility that they form a single conformational epitope. Thus, both repeat regions may serve to deflect the immune response targeted to the functional domain of P.69 pertactin. This may explain why the variation in P.69 pertactin is so effective, despite the fact that it is limited to only two small segments of the molecule.